The Argentinean real exchange misalignment in the pre-crisis - Bénétrix, Agustín S. (2005)
This paper develops and estimates the medium run non stationary Real Exchange Rate (RER) for Argentina and studies the degree of RER misalignment in the period before the abandonment of the Currency Board. Here, two approaches are taken to compute the misalignment: one is to take as reference the RER consistent with Current Account (CA) equal to zero and the other is to take RER consistent with the external debt sustainability. Both measures give important information regarding the probability of the crisis in relation with the degree of RER misalignment.